Evaluasi Program Penilaian Kinerja Guru - Hajar, Encik Abdul; Mukhtar, Mukhneri (JERAM, 2017)
This study is aimed to evaluate the implementation of teacher performance appraisal program in Tanjungpinang City. This study is a qualitative research, using CIPP model.The results of this study concluded about the implementation of teacher performance appraisal program in accordance with the evaluation criteria. Generally the teacher performance appraisal program in junior high schools in Tanjungpinang City was designed well as a quality control system of teaching and learning activity in class. However, this study shows some findings about the implementation of teacher performance appraisal program that do not meet the evaluation criteria.